Livelihood dependency on NTFP's among forest dependent communities: An overview - Doma Lepcha, Lakpa; Shukla, Vineeta Gopal; Chakravarty, Sumit (Indian Forester, 2020)
About 150 to 200 million indigenous or forest dependent communities of over 70 countries, mostly in tropics interact closely with forest especially through Non-timber forest products (NTFPs) to sustain their livelihood, derive their income also their cultural and spiritual identity. NTFPs along with traditional plant based knowledge are deep-rooted among the vast majority of indigenous communities. Reduction in forest cover and land use change has dramatic effect on production and collection of NTFPs worldwide; contributed to climate change and altering ecosystem service. NTFPs have the potential to bring an economic revolution in the lives of the indigenous communities and hold good prospects for upliftment of the forest fringe communities as forests provide 'natural insurance' to these communities. Therefore, exploration and listing of NTFPs with their ethnobiological values are important for knowing and evaluating human plants relationship, potential for their use in day to day life and for proper management. Nationalization of NTFPs may also ensure the welfare of these communities through better remuneration. There exists a huge potential of utilizing traditional ecological knowledge that indigenous communities possess about NTFP resources, their use and management for achieving sustainable NTFP production.